A new supervisory energy managmement control strategy of a modified D-STATCOM configuration and dual DC source in distribution grids. - Al-Kubragyi, Shatha S. (Cranfield University, 2018)
A microgrid is a state-of-the-art, next generation of electric distribution grid that provides a fundamental paradigm shift from passive grid networks to active networks. Power electronic technologies play a vital role in enabling microgrids to meet their system level requirements of power quality, reliability and demand response capability. A conventional distribution static compensator (D-STATCOM) is a power electronic converter which acts as a reactive power compensator and voltage controller at the point of common coupling in a grid system. However, these devices have limited ability to mitigate voltage fluctuations caused by active power disturbances. By integrating energy storage into the DC link of a D-STATCOM, controllable active power from the storage device can result in enhanced voltage compensating capability. The active and reactive power control between the D-STATCOM and AC power point is achieved by suitable tuning of the phase and magnitude of the output voltage of the D-STATCOM’s converter. Recent advances and innovations in energy storage systems such as super-capacitors and batteries allow the combination of battery-supercapacitor hybrid energy storage systems to act as an effective solution for energy management in smart grid operation. However, the concept and control of the hybridisation of energy storage are relatively new, and there are great challenges to the development of control management systems, for example, reduce battery current stresses. This study presents a novel approach in applying a fuzzy-PI controller to a D-STATCOM based energy storage unit to provide enhanced power quality and voltage stability in distribution grids. Full information is provided concerning the implementation of the system, and the dynamic controls devised during the research programme. A second novel approach is the use of sugeno fuzzy logic controller based decision making for power management of the D-STATCOM based HESS to achieve a robust and superior performance for voltage regulation. Recent developments in this field have tended to converge on intelligent control as the best approach to achieve an effective strategy for power sharing with HESSs by using a high-power storage unit (supercapacitor) and high energy storage unit (battery) in combination with the D-STATCOM to avoid the drawbacks of a single storage unit. This development is considered one of the main ways to upgrade energy storage technology, with gains of faster voltage regulation and decreased battery current peak value. Verification of the control designs has been achieved through simulation using MATLAB/SIMULINK based on the derived analytical model in state-space form. Comprehensive simulation results show that the proposed fuzzy controller demonstrates significant improvements over conventional controllers in supporting voltage stability in distribution networks
Keywords: Voltage stability; D-STATCOM; energy storage system; fuzzy logic; microgrid; control management systems; sugeno fuzzy logic